Neonatal lupus erythematosus: Report of a case with cutaneous, hematological and hepatobiliary findings - SALMAN, ANDAÇ; YÜCELTEN, AYŞE DENİZ (TURKISH J PEDIATRICS, 2016)
Neonatal lupus erythematosus is an autoimmune disorder mainly affecting the heart and skin. It is the most common cause of congenital heart block. In addition, hematological, hepatobiliary and neurological involvement may occur. Herein, we report a 23-day-old infant presented with annular, erythematous, and scaly and atrophic lesions on the face and trunk. Based on the clinical, laboratory and histopathological findings, she was diagnosed as neonatal lupus erythematosus. Neonatal lupus eryhtematosus should be considered in infants presenting with annular skin lesions, and we present this case to highlight the value of high index of clinical suspicion in diagnosis.
Keywords: cutaneous; hematological; hepatobiliary; neonatal lupus